PULSE survey: Population Survey on Knowledge, Gaps and Perception of Heart Rhythm disorders-an initiative of the Scientific Initiatives Committee of the European Heart Rhythm Association - Gunawardene, Melanie A; Pürerfellner, Helmut; Merino, Jose L; Linz, Dominik; Sultan, Arian; Scherr, Daniel; Deharo, Jean Claude; Wohlmuth, Peter; Feldhege, Johannes; Costa, Francisco Moscoso; Ribeiro, Silvia; Charitakis, Emmanouil; et al. (Europace, 2025)
AIMS: Despite increasing prevalence, the general population lacks knowledge regarding diagnosis, implications, and management of cardiac arrhythmias (CA). This study aims to assess public perception of CA and identify knowledge gaps. METHODS AND RESULTS: The 36-item PULSE survey was disseminated via social media to the general population and conducted under the auspices of the European Heart Rhythm Association Scientific Initiatives Committee (EHRA SIC) with EHRA patient committee support. Among 3924 participants (2177 healthy, 1747 with previously diagnosed CA; 59% female, 90% European), 81% reported fear of CA. Females were more likely to be 'very' or 'moderately afraid' than males [odds ratio (OR) 1.159 (1.005, 1.337), P = 0.046]. While most recognized complications of CA-heart failure (82%), stroke (80%), and death (75%)-43% were unaware that CA can be asymptomatic. Those with cardiopulmonary resuscitation (CPR) training in the past 5 years were 2.6 times and 4.7 times more confident identifying sudden cardiac death and initiating CPR (P < 0.001). Confidence was lower in retired participants [OR 0.574 (0.499, 0.660), P < 0.001] and Southern Europeans [OR 0.703 (0.600, 0.824), P < 0.001]. Without CPR training, only 15% felt confident initiating CPR. Among CA participants, 28% reported severe to disabling daily symptoms. Males were more often asymptomatic (20% vs. 9%, P < 0.001). Treatment rates were comparable between sex categories (81% vs. 79%, P = 0.413). Interdisciplinary shared decision-making processes were reported by 4%. Notably, 1 in 10 CA cases was self-diagnosed using a wearable device, and 30% of CA participants used smartwatches for self-monitoring. CONCLUSION: Significant knowledge gaps regarding CA exist in the general population. Targeted educational initiatives could be a viable tool to enhance public knowledge, confidence in detecting and managing arrhythmias, particularly for women, who experience greater fear and symptom severity despite similar treatment rates.
Keywords: Atrial fibrillation; sociální média; Fear; Health Surveys; lidé; mladiství; sexuální faktory; Middle Aged; Adult; Pulse; náhlá srdeční smrt; Sex Factors; Risk Factors; strach; Female; Evropa; průzkumy a dotazníky; Adolescent; Humans; Awareness; Death, Sudden, Cardiac; Cardiac arrhythmias; Social Media; lidé středního věku; zdraví - znalosti, postoje, praxe; srdeční arytmie; mužské pohlaví; mladý dospělý; Sudden cardiac death; Arrhythmias, Cardiac; ženské pohlaví; Young Adult; zdravotnické přehledy; Male; Cardiac resuscitation; Aged; Europe; Health Knowledge, Attitudes, Practice; dospělí; Surveys and Questionnaires; rizikové faktory; senioři